Perencanaan Teknis Penyediaan Distribusi Jaringan Air bersih di Daerah Kecamatan Kenohan, Kutai Kartanegara - Sari, Dharwati P; Salasa, Bernardo Sandrini; Utomo, Pandu K.; Putri, Resty Intan; Akhmad, Nuralam (Retii, 2023)
Tuana Tuha Village in Kenohan District is one of the villages in flat topography area and near the ocean with the average population working as fishermen and farmers. To meet drinking water needs, residents buy bottled water regularly. Based on the fact that the need for water will always increase by the time, this community service activity was carried out to help provide drinking water for the residents of Tuana Tuha Village through the provision of clean water. This activity was carried out in several stages, including the preparation, design and implementation, and socialization. The results of this community service activity include identifying the community's main needs for access to clean water in Kenohan District and comprehensive technical planning. The socialization has succeeded in increasing community awareness and participation in the implementation of clean water distribution with inclusive access for residents.